The efficacy of infrared diode laser in enhancing the regenerative potential of human periodontal ligament stem cells (hPDLSCs) - Mohamed M. Abo El-Dahab; Ghada Nour El Deen; Mahmoud Shalash; Mostafa Gheith; Ahmed Abbass; Riham M. Aly (BMC, 2024)
Abstract Background The present study aimed to investigate the effects of infrared diode laser irradiation on the proliferation and differentiation capacity of periodontal ligament stem cells (hPDLSCs), which are optimal cell sources for periodontal regeneration. Methods hPDLSCs were isolated and characterized by flow cytometric analysis of mesenchymal stem cell markers, and their trilineage differentiation capacity was tested. hPDLSCs were then cultured and irradiated with infrared diode laser (970 nm) at a power of 200 mW and a fluence of 4 J/cm2 for 3 s. MTT assay was performed to assess cellular proliferation. Cell cycle analysis was performed, and the impact of infrared diode laser irradiation on the stemness and osteogenic differentiation potential of hPDLSCs was evaluated via RT‒PCR. Results Infrared diode laser application enhanced the stemness, viability, proliferation, and differentiation of PDLSCs. Stem cell markers (OCT4, SOX2, and NANOG) were significantly upregulated in hPDLSCs exposed to laser irradiation. There was significant overexpression of RUNX2, ALP, OPN, and OCN on day 14 after laser application. Conclusions These findings provide valuable insights into the specific applications of infrared diode lasers to effectively regenerate periodontal tissues. The results can aid in the development of precise clinical protocols aimed at enhancing osseointegration and promoting tissue regeneration. Ultimately, the combination of infrared diode laser with hPDLSCs is promising for stimulating periodontal regeneration.